The Abuses of Power in Autobiography (2022) Film Directed by Makbul Mubarak - Rafi Akbar Anandyantoro; Juliati Juliati (Jurnal Pendidikan dan Sastra Inggris, 2026)
Film effectively addresses social issues by exploring inequity, justice, and cultural conflict through visual and narrative storytelling. The Indonesian film Autobiography (2022) examines complex power relations within a sociopolitical context. It follows Rakib, a young man who works for Purna, a retired military general previously served by Rakib’s father, and gradually witnesses how Purna exploits his authority. This study analyzes the representation of power abuse in Makbul Mubarak’s Autobiography using a qualitative approach through scene analysis and thematic review. Louis Althusser’s theories of Repressive State Apparatuses (RSAs) and Ideological State Apparatuses (ISAs) provide the theoretical framework for examining how authority is exercised through narrative, visual elements, and character interactions. The findings reveal that Purna employs ISAs by manipulating villagers to encourage obedience through social manipulation, interpellation, and subtle influence, reinforcing hierarchy and nepotistic corruption. He also exercises RSAs by using intimidation, direct violence, and verbal abuse to maintain control after his military career. Future research could examine the relationship between ruling and subordinate classes in Autobiography through Marxist theory to better understand class-based power dynamics. Additionally, applying Althusser’s ISA theory to Kupu Kupu Kertas (2024) may provide further insights into ideological influence and power structures in 1960s Indonesia.